Organic thin-film transistors with bilayer of rubbed and evaporated hydrocarbon-based acene as active layer. (15th March 2017) - Funada, Shunpei; Shaari, Safizan; Naka, Shigeki; Okada, Hiroyuki
Abstract: We have investigated organic thin-film transistors (OTFTs) with a bilayer of rubbed and evaporated hydrocarbon-based acene 2, 7-dioctyl[1]benzothieno[3, 2-b][1]benzothiophene (C8-BTBT) as an active layer. Using a rubbing process after spin-coating the C8-BTBT, crystallinity of the C8-BTBT thin film was improved and resultant superior OTFT characteristics were realized. We obtained a field-effect mobility of 1.6 cm 2 /Vs, a threshold voltage of −8.2 V, an on-off ratio of 10 6, and a subthreshold swing of 55 mV/decade.